Chapter Measuring content validity of academic psychological capital and locus of control in fresh graduates - Anselmi, Pasquale (Proceedings e report, 2021)
Positive psychological capital (PsyCap; hope, resilience, self-efficacy, and optimism) and locus of control (LoC; internal and external) denote psychological dimensions which have been identified as crucial resources for occupational satisfaction and success. These dimensions could impact fresh graduates' ability to stand the labour market in times of crisis. Two instruments, called Academic PsyCap and Academic LoC, have been specifically developed to evaluate these dimensions among fresh graduates. The two instruments consist of 34 and 10 items respectively, which have been selected, through factor analyses, from a large initial pool of items administered to fresh graduated at the University of Padova. Results suggested adequate psychometric properties for both Academic PsyCap and Academic LoC. The factor structure of the two instruments was confirmed (CFI = .92, RMSEA = .07, SRMR = .07 for Academic PsyCap; CFI = .96, RMSEA = .05, SRMR = .05 for Academic LoC), and internal consistency was satisfactory for all the subscales. The two instruments are presented, and their psychometric properties are described.